Penerapan Abdominal Stretching Exercise Terhadap Dismenore Pada Remaja Putri - Setianingsih, Eva; Dewi, Rusmala; Mulia, Madepan (Bunda Edu-Midwifery Journal (BEMJ), 2022)
Teenage is also known as puberty, the term puberty is also used to express physiological changes that occur rapidly from childhood to adulthood, especially changes in the reproductive organs. One of the secondary characteristic changes in women is menstruation. Menstruation is regular bleeding from the uterus as a sign that the uterine organs have begun to function properly. Menstruation for every teenager is different, some menstruate without problems and disturbances, but there are also those with problems such as dysmenorrhea or pain during menstruation. This study aims to determine the description of the application of abdominal stretching exercise to reduce pain in dysmenorrhea. This research is a descriptive study with a population of young women experiencing dysmenorrhea in the working area of ​​Way Kandis Health Center 2020. The results showed that there was a decrease in the level of pain in dysmenorrheal by using the application of abdominal stretching exercises on the first participant on average before being given the application, namely a pain scale of 5 (moderate) and the second participant on a pain scale of 4 (moderate), and after being given the application of abdominal stretching exercise the average of the first participant was on a pain scale of 3 (low) and the second participant on a pain scale of 2 (low).